An integrative risk assessment approach to enhancing patient safety in Continuous Renal Replacement Therapy (CRRT) - Ahmed Saad; Juman Alsadi; Dima Tareq Al-Absi; Muhra Almulla; Mecit Can Emre Simsekler; Ahmed Adel Sadeq; Fahad Omar; Mazhar Basha; Islam Khatab; Noha Abu Khater; Andrea Molesi; Siddiq Anwar (Journal of Safety Science and Resilience, 2024)
Continuous Renal Replacement Therapy (CRRT) serves as an intervention strategy for the management of acute kidney injury (AKI) in critically ill patients. However, owing to its complex nature and the potential for complications, the implementation of CRRT demands continuous monitoring to prevent patient safety risks. This study aims to identify and validate prevalent risks linked to CRRT within a real-world clinical setting, intending to propose preventive measures grounded in expert insights. To systematically categorize and visually depict the risks, their consequences, preventive measures, and recovery controls, our study employed the Bowtie method in conjunction with the Systems Engineering Initiative for Patient Safety (SEIPS) model. In addition to considering patient-related factors that exhibit variability among critically ill individuals, our key findings showed that the most influential risks impacting the effective delivery of CRRT are incidents of clotted filters, bleeding risks arising from the necessity of anticoagulation for filter efficacy, vascular catheter-related bloodstream infections, variations in proficiency levels among healthcare professionals regarding CRRT modalities, especially in operating the CRRT machines, high nursing workload, frequent nursing turnover, occurrences of hypophosphatemia, variability in CRRT prescribing patterns, and issues related to communication among stakeholders. This research sheds light on the primary risks associated with CRRT and provides practical and viable strategies for effective management. Furthermore, the Bowtie diagram developed as part of this study serves as a valuable tool for visually representing the healthcare system and facilitating the identification of system-related risks within healthcare settings.